Sikap Remaja Dalam Prinsip-Prinsip Komunikasi Islam terhadap Orang Tua di Desa Jaharun Kecamatan Galang - Amin, Afriadi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to find out how the attitude of adolescents towards their parents, in the principles of Islamic communication in Jaharun Village, Galang District. This is motivated by the lack of awareness of adolescents in communication ethics. In general, everyone must have communication ethics, because communication is the most important thing in the life of every human being. This study uses a descriptive qualitative approach. The data we collected used the interview and observation stages. After this data was obtained, we carried out this analysis using the tabularasa theory. The results of this study turned out that the attitudes and communication ethics of adolescents were not in accordance with the principles of Islamic communication. Therefore, the effort that can be made for the awareness of youth in Jaharun village is to mobilize and provide motivation through activities related to good communication. In addition, the assemblies in Jaharun Village must also be developed and revived, by inviting all youth to attend every recitation held by the assemblies. Keywords: The principles of Islamic communication, parents, youth